(untitled) (Andamios, Revista de Investigación Social, 2025)
This paper will analyse the interpretative frameworks, and their most common recombinations, used by young women to make sense of their experiences of gender inequality in the context of entrepreneurship. These frameworks enable the mobilisation and legitimisation of certain ways of conducting themselves as entrepreneurs and, consequently, enable and contribute to a certain subjective self-production through techniques of the self. With this aim, 30 female entrepreneurs under 35 years who participate or previously participated in training programmes for women entrepreneurs in Spain were interviewed. They also came from different socio-structural backgrounds in Spain, and were at different stages of their entrepreneurial trajectory, with ventures in diverse areas of knowledge. Four main interpretative frameworks were identified: psychologicist, culturalist, structuralist and non-recognition of inequalities.